(untitled) (Research, Society and Development, 2022)
Introduction: Cervical cancer is a neoplasm that begins as a precursor lesion that may or may not evolve into an invasive process. Different signs and symptoms can indicate its appearance, but it is a preventable and curable condition when diagnosed early. Objective: To analyze the possible most prevalent signs and symptoms in cervical cancer screening in primary health care (PHC). Method: This is an integrative review. The PRISMA instrument was used to write the study. The searches were carried out in three databases, resulting in 1002 studies, of which 7 were eligible to compose the final sample. A descriptive analysis of the data was performed. Results: Most of the included studies were developed in South Africa and published in 2020. Intermittent vaginal bleeding and vaginal bleeding during or after sex (100%), abnormal vaginal discharge (85,7%), pain and/or discomfort during gender (42,8%), and intermittent and/or persistent lower abdominal pain (28,5%) were identified as the main possible predictive signs and symptoms of cervical cancer in primary care. Other symptoms were evidenced less frequently within the sample. Conclusion: The study provided a descriptive integration of the main clinical manifestations characteristic for the development of cervical cancer, contributing to the expansion of the knowledge of students and professionals in this area and subsidizing the scientific production and provision of care in Primary Care.